2013
DOI: 10.1111/jawr.12100
|View full text |Cite
|
Sign up to set email alerts
|

A Decade of Geomorphic and Hydraulic Response to the La Valle Dam Project, Baraboo River, Wisconsin

Abstract: We investigate stream response to the La Valle Dam removal and channel reconstruction by estimating channel hydraulic parameter values and changes in sedimentation within the reservoir. The designed channel reconstruction after the dam removal included placement of a riffle structure at the former dam site. Stream surveys undertaken in 1984 by Federal Emergency Management Agency and in 2001 by Doyle et al. were supplemented with surveys in 2009 and 2011 to study the effects of the instream structure. We create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In some cases, post-removal sediment management was performed to slow or stop channel widening or grade control was placed at the dam site to limit erosion. In the cases reviewed, unanticipated storage and fining of new sediment occurred once the dam was removed because of the replacement of the baselevel control, which, in one case, impacted the project's ability to meet restoration goals (Greene et al, 2013). Use of a grade control may only be warranted when excessive downstream channel incision has occurred that could propagate upstream or consequences of additional sediment release are not tolerable.…”
Section: Excessive Channel Incision Upstream Of Reservoirsmentioning
confidence: 99%
“…In some cases, post-removal sediment management was performed to slow or stop channel widening or grade control was placed at the dam site to limit erosion. In the cases reviewed, unanticipated storage and fining of new sediment occurred once the dam was removed because of the replacement of the baselevel control, which, in one case, impacted the project's ability to meet restoration goals (Greene et al, 2013). Use of a grade control may only be warranted when excessive downstream channel incision has occurred that could propagate upstream or consequences of additional sediment release are not tolerable.…”
Section: Excessive Channel Incision Upstream Of Reservoirsmentioning
confidence: 99%
“…Thus, while apparent cohesion associated with negative pore pressures (i.e., matric suction) can produce very stable banks in unsaturated streambanks (Rinaldi & Darby, 2008), apparent cohesion was considered to be zero in all model simulations because soils remained saturated and the region above the groundwater table was sufficiently small with respect to saturated height. We speculate that the slow erosion rates observed at some dam removals with fine sediments (Doyle et al, 2003; Foley et al, 2017; Greene et al, 2013; Kosky et al, 2004; Randle et al, 2015; Tullos et al, 2016) are associated with higher hydraulic conductivities relative to the drawdown rates that produced unsaturated, drained conditions. However, the stabilizing effect of establishing drained conditions, even in saturated soils, is illustrated by the design of staged drawdowns of fine‐grained reservoirs at Elwha, Glines Canyon, and Brewster Dam in an attempt to reduce the magnitude and/or rate of erosion (Major et al, 2017).…”
Section: Discussionmentioning
confidence: 84%
“…Regularly dewatered reservoirs had little consolidated or coarse sediment and rapidly eroded following dam removal, while contrasting sites with consolidated fine sediment exhibited limited headcut migration and, therefore, slower channel evolution. Hydraulic and geomorphologic modeling by Greene et al (2013) demonstrated that post-dam-removal management greatly influences channel dynamics. Their modeling work predicts that bank stabilization that created a riffle structure following the La Valle Dam removal on the Baraboo River, Wisconsin has long-term implications for sediment transport.…”
Section: Channel Formationmentioning
confidence: 99%